PISA design model for monopiles for offshore wind turbines: application to a stiff glacial clay till - Byrne,BW; Houlsby,GT; Burd,HJ; Gavin,K; Igoe,D; Jardine,RJ; Martin,CM; McAdam,RA; Potts,DM; Taborda,D; Zdravkovic,L (Geotechnique, 2020)
Offshore wind turbines in shallow coastal waters are typically supported on monopile foundations.Although three dimensional (3D) finite element methods are available for the design of monopiles inthis context, much of the routine design work is currently conducted using simplified one dimensional(1D) models based on the p-y method. The p-y method was originally developed for the relativelylarge embedded length-to-diameter ratio (L/D) piles that are typically employed in offshore oil and gasstructures. Concerns exist, however, that this analysis approach may not be appropriate formonopiles with the relatively low values of L/D that are typically adopted for offshore wind turbinestructures. This paper describes a new 1D design model for monopile foundations; the model isspecifically formulated for offshore wind turbine applications although the general approach could beadopted for other applications. The model draws on the conventional p-y approach, but extends it toinclude additional components of soil reaction that act on the pile. The 1D model is calibrated using aset of bespoke 3D finite element analyses of monopile performance, for pile characteristics andloading conditions that span a predefined design space. The calibrated 1D model provides results thatmatch those obtained from the 3D finite element calibration analysis, but at a fraction of thecomputational cost. Moreover, within the calibration space, the 1D model is capable of delivering highfidelity computations of monopile performance that can be used directly for design purposes. This 1Dmodelling approach is demonstrated for monopiles installed in a stiff overconsolidated glacial clay tillwith a typical North Sea strength and stiffness profile. Although the current form of the model hasbeen developed for homogeneous soil and monotonic loading, it forms a basis from which extensionsfor soil layering and cyclic loading can be developed. The general approach can be applied to otherfoundation and soil-structu